Effect of garlic genotypes (Allium sativum L.) on phenotype, growth, yield-related attributes, and nutritional quality at Bule Hora agro-ecology - Gebre Garmame Galgaye (Heliyon, 2023)
Inappropriate variety use in different agroecology is one of the primary issues which significantly affect garlic phenotype, growth, yield, and nutritional quality. For this reason, a trial was done during the 2022 main season at the demonstration site of Bule Hora University, to see the impact of genotypes on phenotype, growth, yield-related attributes, and nutritional quality of garlic. The experiment was composed of four varieties namely Kuriftu, Holleta, Chafe, Tsedey 92, and one local cultivar. The trial was set up in a randomized complete block design replicated four times. The output showed that garlic varieties statistically (p < 0.05) affected all phenotype, growth, yield-related attributes, and nutritional qualities. Using a variety of Holleta and kuriftu minimize days of emergence by 9.82 and 10.33 days after planting and 75% physiological maturity by 23.6 and 25.90 days after planting, respectively, beyond variety Tsedey 92. The highest marketable bulb yield (8.21 t/ha, and 8.18 t/ha) was observed from Kuriftu and Holleta, respectively. While the lowest (4.39 t/ha) was from Tsedey 92. The highest Ash, energy, and carbohydrate were recorded from Kuriftu and Holleta, while the least from the Local cultivar. However, the highest moisture content, protein, and fat were observed from local cultivars, while the least from Kuriftu, and Holleta. In general, garlic varieties significantly affected all the phenotype, growth, bulb yield-related, and Nutritional quality. Therefore, it can be concluded that using the variety Kuriftu, and Holleta at Bule Hora agroecology is suggested to boost early germination, better performance, marketable bulb yield, and nutritional quality of garlic.